Time Determination of Gas Extraction in Coal Seam Drilling. Issue 4 (April 2020) - Hong, Ding; Dong, Wang
Abstract: In order to determine the time of the gas extraction of the solid unstable coal seam, based on the characteristics of the change of gas concentration under the condition of continuous extraction of high negative pressure, the drilling gas parameters were tested on the spot and the gas concentration attenuation curve was drawn, and the law of attenuation of the drilling gas concentration was analyzed comprehensively using gas flow theory and geomechanics-related theory. The results show that the interval between the detection and drainage is 0 to 60d, the time of the extraction is 3d, the time of extraction is 60 to 120d, the time of the water testing interval is 7d, the extraction time is 120 to 180d, the time of the water testing interval is 15d, and the extraction time is 180 to 300d. The interval between the measurement of the flow is 30d.